Microbial contamination of heating, ventilation and air conditioning (HVAC) systems and the efficiency of various filter types in trapping microorganisms in Eastern Saudi Arabia - Al-Abkari, Hmidah Abdulhadi; Al-Abdalall, Amira Hassan (2017)
This study aimed to isolate the bacteria and fungi in air conditioning (AC) systems in different types of building during the four seasonal climates and to show the efficiency of various filters used for trapping the microorganisms. Samples of dust were collected from
two different types of AC systems from various buildings followed by inoculation of the samples in different types of enrichment media. The frequency distribution of isolates were calculated during the four seasons. AC systems were found to be contaminated by different types of bacterial and fungal species. Specifically, the bacterial species isolated included Serratia liquefaciens, Bacillus pumlilus, B. cereus, B. subtilis, Staphylococcus lentus and Oligella ureolytica. The common fungal taxa that were found included Cryptococcus laurenti, Asperigillus niger, A. flavus, Claddosporium sp. and Rhizoctonia sp. The results demonstrated that buildings, which were in good condition, were the ones most commonly contaminated which microorganisms. Dammam Province had the higher percentage of contaminated in shopping centers compared to the nearby province of Qatif. However, Qatif had higher levels of contamination in homes, educational centers and school compared to Dammam. Window-type air conditioning units were showed to harbor more bacteria and fungi compared to evaporative cooling systems in both provinces. This study examined the most commonly used filters for purifying air conditioning systems including sponge, polyester, HEPA,and complex filters. Their ability to prevent bacteria and fungi from passing through the AC systems were estimated. Complex filters showed to be more efficient in purifying the air with estimated rates of 91.8% for the bacteria and 100% for fungi. In contrast, sponge filter was the least efficient with estimated rates of 2 and 50% for bacteria and fungi, respectively.
Keywords: Air filters